The Effect of the Managers’ Good Manners on Enhancing the Social Responsibility of the Staff from Agriculture Banks in Sistan and Baluchistan - Mohammad Mostafa Dahmardeh (Journal of Global Pharma Technology, 2017)
Efforts to improve human resource Responsibility and efficient use of human resources infinite, timeless way. In this way, ups and downs, one of the goals of efficiency, increase the desirability of life with all its dimensions. In this study, researchers are sought to The Effect of the Managers’ Good Manners on Enhancing the Social Responsibility of the Staff from Agriculture Banks in Sistan and Baluchistan. The research is descriptive and correlational. The target population included 419 Staff from Agriculture Banks in Sistan and Baluchistan. That uses Morgan table, 201 individuals were selected as sample. Library and field data collection for studies of Managers’ Good Manners questionnaire that standard questionnaire [1] and Social Responsibility questionnaire is self-made. Its validity and reliability have been approved. For data analysis using SPSS software, descriptive and inferential analysis (linear regression) is used. The results show that the Managers’ Good Manners and its components have an impact on Social Responsibility.